2017
DOI: 10.1007/s11356-017-0372-9
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregate and organic carbon distribution at dry land soil and paddy soil: the role of different straws returning

Abstract: Agriculture wastes returning to soil is one of common ways to reuse crop straws in China. The returned straws are expected to improve the fertility and structural stability of soil during the degradation of straw it selves. The in situ effect of different straw (wheat, rice, maize, rape, and broad bean) applications for soil aggregate stability and soil organic carbon (SOC) distribution were studied at both dry land soil and paddy soil in this study. Wet sieving procedures were used to separate soil aggregate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
40
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 57 publications
7
40
1
1
Order By: Relevance
“…We observed that high amounts of straw addition decreased the mass proportion of the silt plus clay fraction and increased the mass proportion of large macroaggregates but had no effect on the mass proportions of small macroaggregates and microaggregates (Table ). This result is consistent with Huang, Lan, Liu, and Gao (), Long et al. () and Garcia‐Franco, Albaladejo, Almagro, and Martínez‐Mena () who found that straw amendments increased the fractions of large and small macroaggregates (>0.25 mm) and microaggregates (0.25–0.053 mm) and reduced the proportion of microaggregates and the silt plus clay fraction.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that high amounts of straw addition decreased the mass proportion of the silt plus clay fraction and increased the mass proportion of large macroaggregates but had no effect on the mass proportions of small macroaggregates and microaggregates (Table ). This result is consistent with Huang, Lan, Liu, and Gao (), Long et al. () and Garcia‐Franco, Albaladejo, Almagro, and Martínez‐Mena () who found that straw amendments increased the fractions of large and small macroaggregates (>0.25 mm) and microaggregates (0.25–0.053 mm) and reduced the proportion of microaggregates and the silt plus clay fraction.…”
Section: Discussionsupporting
confidence: 90%
“…Correspondingly, the incorporation of straw could lead to soil particles to stick together, which in turn, form soil aggregates. Similar results have been reported [14,[53][54][55].…”
Section: Influence Of Fertilizer On Soil Propertiessupporting
confidence: 91%
“…The available phosphorus (AP) content was extracted by a 0.5 mol L −1 NaHCO 3 (pH 8.5) solution. The available potassium (AK) content was extracted by using 1 mol L −1 NH 4 Ac (pH 7.0) [39]. The soil organic carbon (SOC) was determined by K 2 Cr 2 O 7 oxidation and FeSO 4 titration [40].…”
Section: Soil Propertiesmentioning
confidence: 99%